2020
DOI: 10.1016/j.advwatres.2020.103528
|View full text |Cite
|
Sign up to set email alerts
|

Comparing global hydrological models and combining them with GRACE by dynamic model data averaging (DMDA)

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 100 publications
0
26
0
Order By: Relevance
“…In the light of our results in the previous section, we believe that the reconstruction results from Approach 2 have better quality, i.e., contain less noise and the mass anomalies are well localized. Therefore, these fields are used to assess the global mass redistribution of 2003-2018 in terms of trends, seasonal and sub-seasonal cycles, as well as those related to teleconnection evens, see similar studies, e.g., [14,44,50,56,78]. To illustrate the benefit of the iterations in Approach 2 to reduce the noise in TWSC fields, a comparison between the results of the first iteration with those of 250th iteration in terms of basin-averaged TWSC is shown in Figure A1.…”
Section: 7082mentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of our results in the previous section, we believe that the reconstruction results from Approach 2 have better quality, i.e., contain less noise and the mass anomalies are well localized. Therefore, these fields are used to assess the global mass redistribution of 2003-2018 in terms of trends, seasonal and sub-seasonal cycles, as well as those related to teleconnection evens, see similar studies, e.g., [14,44,50,56,78]. To illustrate the benefit of the iterations in Approach 2 to reduce the noise in TWSC fields, a comparison between the results of the first iteration with those of 250th iteration in terms of basin-averaged TWSC is shown in Figure A1.…”
Section: 7082mentioning
confidence: 99%
“…Validating GRACE TWSC fields was performed by comparisons with geophysically relevant signals from independent data sources. For example, hydrological models were used to assess GRACE data over land area (e.g., [9,49]); however, many studies, e.g., [16,50], indicate that the trend and seasonality of these models are uncertain and such comparisons might be performed with care. Other studies, e.g., [51][52][53] suggested the use of in-situ data such as ocean bottom pressure and global navigation satellite systems (GNSS)-derived vertical loads to assess GRACE signals.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most studies mainly rely on a single hydrological model to separate GWS components from GRACE-derived TWS [23][24][25]. However, the accuracy of these models is restricted by uncertainties in climate forcing (particularly precipitation), model parameters, and deficiencies in model structure [26][27][28][29][30][31]. Therefore, the effective combination of multiple models can improve the performance of hydrological simulations relative to a single model.…”
Section: Introductionmentioning
confidence: 99%
“…Long et al [33] used the Bayesian model-averaging technique, which can merge multiple TWS products to analyze the spatiotemporal variability of TWS. Mehrnegar [27] presented the dynamic model-data-averaging method, which can be used to merge multiple TWS simulations. The result indicated that linear trends and seasonality within global hydrological models can be improved by using the dynamic model-dataaveraging method.…”
Section: Introductionmentioning
confidence: 99%
“…GRACE and GLDAS (Global Land Data Assimilation System) have provided useful observations for studying water resources around the world, particularly over regions with insufficient in-situ measurements (e.g., Chen et al, 2019;Scanlon et al, 2018). Recently several studies (e.g., Hasan et al, 2018;Mehrnegar et al, 2020;Seyoum, 2018;Shamsudduha et al, 2017) have used GRACE observations to explore changes in TWS in the Nile River Basin (NRB).…”
mentioning
confidence: 99%